Er Miao San, a traditional Chinese herbal formula, attenuates complete Freund's adjuvant-induced arthritis in rats by regulating Th17/Treg cells. (1st January 2020) - Dai, Xing; Yang, Dongping; Bao, Jinping; Zhang, Qiying; Ding, Jiemin; Liu, Min; Ding, Meihuizi; Liu, Mengli; Liang, Juan; Jia, Xiaoyi
Abstract: Context: Er Miao San (EMS) is a traditional Chinese medicine composed of Atractylodis Rhizoma and Phellodendri Cortex in a 1:1 weight ratio. EMS has been used to treat rheumatism in China for many years. Objective: To evaluate the anti-arthritic activity of EMS extract on adjuvant-induced arthritis (AA) in Sprague-Dawley rats and to clarify its mechanisms of action. Materials and methods: EMS (0.75, 1.5 and 3 g/kg, once daily) was orally administered from day 18 after immunization to day 31. The effects of EMS on AA rats were evaluated by histopathological examination, paw swelling and polyarthritis index. The proliferation of fibroblast-like synoviocyte (FLS) and T cells was detected by CCK-8. The percentages of Th17 cells and Treg cells in splenocytes were determined by flow cytometry. Levels of cytokines in serum were detected by ELISA. Results: EMS treatment significantly decreased the paw volume (from 1.20 to 0.81), polyarthritis index (from 9.56 to 4.46) and alleviated ankle joint histopathology in AA rats. EMS inhibited the proliferation of FLS and T cells. Furthermore, EMS treatment decreased Th17 cells (from 4.62 to 2.08%) and increased Treg cells (from 2.77 to 4.75%) in splenocytes. The levels of IL-17A, TNF-α and IL-6 were remarkably decreased in the serum of EMS-treated rats, whereas the levels of IL-10 and TGF-β1 were significantly increased. Conclusions: EMS exhibits anti-arthritic activity in the AA model by regulating the balance of cytokines and the ratio of Th17 and Treg cells. These insights may provide an experimental basis for the clinical treatment of RA.